Innovations in Spinal Muscular Atrophy: From Gene Therapy to Disease-Modifying Treatments (International Journal of Engineering and Computer Science, 2021)
While the recent development of disease-modifying treatments for spinal muscular atrophy arose from an understanding of scheme function, the achievement of adequate motor neuron molecule availability and proprioceptive feedback has always been crucial for the preservation of function and fitness of muscle units in childhood. Progress in neuroscience research, its methods, applications, and outcomes, together with growing interest in rare diseases, has considerably improved at least the length and quality of life in subjects affected by the most severe forms of spinal muscular atrophy, and for several of those with intermediate or later-onset (or milder) forms. Therefore, what had been for a long time predominantly a familial, parent-proven strategy, aimed at the optimization of rehabilitation and caring, and at the prevention of chronic complications chronically affecting the quality of life of subjects with more severe forms of spinal muscular atrophy, has now turned into a more multidisciplinary, hospital-coordinated and longer-term vision of spinal muscular atrophy management. This paper aims to present a practical description of the tools available today for the rehabilitation and management of spinal muscular atrophy patients from a motor, orthopedic, and cardiopulmonary perspective. Disease-modifying spinal muscular atrophy treatment with real-life effects will be discussed wherever available. Spinal muscular atrophy motor function, fitness, and quality of life are highly interdependent. Hence, optimizing management in the three connected areas may help in achieving a better quality of life for the individual patient. Achieving this objective with a multidisciplinary team possibly performed in the same location with the patients might bring improvement to the patients and families involved.